Endoscopic treatment of early oesophageal or gastric cancer. Issue 1 (January 1997) - Takeshita, K; Tani, M; Inoue, H; Saeki, I; Hayashi, S; Honda, T; Kando, F; Saito, N; Endo, M
Abstract : BACKGROUND AND AIMS: Endoscopic treatment has become increasingly popular in recent years as an alternative to surgical treatment with the hope of offering superior quality of life (QOL) for the patient. The results of endoscopic treatment of mucosal lesions of mostly early oesophageal or gastric cancer performed in 145 patients (155 lesions) over the past eight years were reviewed from the standpoint of QOL. RESULTS: In 56 patients who underwent radical resection of the oesophageal mucosa, no serious complications and symptoms occurred, with epithelialisation completed within about a month. Patients also showed good results regarding dietary intake and performance status (PS), and all are currently alive without any sign of recurrence. One time fractionated endoscopic resection was carried out in about 40% of the 57 patients who underwent gastric mucosal resection. In these 57 patients, an artificial ulcer measuring 3 cm or more was formed, resulting in a favourable outcome after healing. An overwhelming proportion of these subjects had no symptoms and good PS after the treatment. CONCLUSIONS: The introduction of this method, endoscopic mucosal resection using a cap fitted panendoscope, is expected to permit additional indications for endoscopic treatment. Endoscopic Nd-YAG laser irradiation was applied mainly to early gastric cancer lesions (32 patients), usually for relative indications for endoscopic treatment. This procedure is safe and advantageous in that it requires no hospitalisation, permits fractionated irradiation, and secures good QOL.